Fatty acid oxidation is required for active and quiescent brown adipose tissue maintenance and thermogenic programing - Elsie Gonzalez-Hurtado; Jieun Lee; Joseph Choi; Michael J. Wolfgang (Elsevier, 2018)
Objective: To determine the role of fatty acid oxidation on the cellular, molecular, and physiologic response of brown adipose tissue to disparate paradigms of chronic thermogenic stimulation. Methods: Mice with an adipose-specific loss of Carnitine Palmitoyltransferase 2 (Cpt2A−/−), that lack mitochondrial long chain fatty acid β-oxidation, were subjected to environmental and pharmacologic interventions known to promote thermogenic programming in adipose tissue. Results: Chronic administration of β3-adrenergic (CL-316243) or thyroid hormone (GC-1) agonists induced a loss of BAT morphology and UCP1 expression in Cpt2A−/− mice. Fatty acid oxidation was also required for the browning of white adipose tissue (WAT) and the induction of UCP1 in WAT. In contrast, chronic cold (15 °C) stimulation induced UCP1 and thermogenic programming in both control and Cpt2A−/− adipose tissue albeit to a lesser extent in Cpt2A−/− mice. However, thermoneutral housing also induced the loss of UCP1 and BAT morphology in Cpt2A−/− mice. Therefore, adipose fatty acid oxidation is required for both the acute agonist-induced activation of BAT and the maintenance of quiescent BAT. Consistent with this data, Cpt2A−/− BAT exhibited increased macrophage infiltration, inflammation and fibrosis irrespective of BAT activation. Finally, obese Cpt2A−/− mice housed at thermoneutrality exhibited a loss of interscapular BAT and were refractory to β3-adrenergic-induced energy expenditure and weight loss. Conclusion: Mitochondrial long chain fatty acid β-oxidation is critical for the maintenance of the brown adipocyte phenotype both during times of activation and quiescence. Keywords: Fatty acid oxidation, Brown adipose tissue, Cold induced thermogenesis, Adrenergic signaling, Adipose macrophage